Estudo da tensão média de escoamento de aços laminados em tiras a quente - Altair Lucio de Souza (2010)
The deformation resistances during the hot strip mill process of four groups of steels (C-Mn; Interstitial Free; HSLA Nb-microalloyed and Ultra Low Carbon Si-alloying and addition of Al) were investigated through the calculation of the mean flow stress from industrial data obtained in the rolling mills of Usiminas, using the methods of Sims, Misaka and Shida. For evaluation of the effect of the chemical elements, the groups were divided in three subgroups with alteration of the level of chemical elements keys of each group. The results showed that for steels processed in the Roughing Mill in the austenitic phase (groups 1, 2 and 3), that correspond to most of the steels types processed in the hot strip mill, the microalloying elements had no significant interference in the mean flow stress and the methods of Misaka and Shida led to results very close to the reference values of the process. For steels processed in the intercritical phase in this stage (group 4), Shidas and Misakas equations overestimated the values of the mean flow stress. In the Finishing Mill, with the decrease of the temperature and time between passes, the increase of deformation rate and precipitate formation due to presence of microalloying elements, the studied methods did not describe adequately the behavior of the mean flow stress in the rolling pass indicating the need for introduction of coefficients for correction when applied in the industrial process.